Reduced-Complexity MIMO Faster-Than-Nyquist Signaling Transceiver for OTFS Modulation - Zekun Hong; Shinya Sugiura (IEEE Open Journal of the Communications Society)
This paper proposes a novel reduced-complexity detection scheme for multiple-input multiple-output (MIMO)-assisted faster-than-Nyquist (FTN) signaling scheme in the frequency selective fading channels. By utilizing the channel’s circulant approximation, we exploit fast Fourier transform (FFT)-aided diagonalization and linear minimum mean square error (LMMSE) algorithm with a log-linear complexity. The proposed scheme achieves the same bit error rate (BER) performance as the conventional LMMSE detector while attaining a significantly lower complexity. Furthermore, we propose the amalgamation of MIMO-FTN signaling and orthogonal time frequency space (OTFS) modulation and conceive the low-complexity delay-Doppler-domain detection algorithm by exploiting the channel’s sparsity. Our performance results demonstrate that the proposed MIMO-FTN and MIMO-OTFS-FTN signaling schemes exhibit a higher information rate and than the conventional Nyquist-based counterparts using the same root-raised-cosine shaping filter.